2022
DOI: 10.1371/journal.pone.0269462
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of a prognostic signature related to hypoxic tumor microenvironment in cervical cancer

Abstract: Background Hypoxia is a common microenvironment condition in most malignant tumors and has been shown to be associated with adverse outcomes of cervical cancer patients. In this study, we investigated the effects of hypoxia-related genes on tumor progress to characterize the tumor hypoxic microenvironment. Methods We retrieved a set of hypoxia-related genes from the Molecular Signatures Database and evaluated their prognostic value for cervical cancer. A hypoxia-based prognostic signature for cervical cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…In predicting CESC prognosis, the AUC value of this risk model was relatively high, at 0.727. Compared with previous cervical cancer biomarkers, although the AUC value of our risk model is not the highest, similar to many previous risk models, our risk model can not only predict prognosis better but also serves as an independent prognostic model [48][49][50][51]. These results also suggest that we may need to further refine our models.…”
Section: Discussionsupporting
confidence: 67%
“…In predicting CESC prognosis, the AUC value of this risk model was relatively high, at 0.727. Compared with previous cervical cancer biomarkers, although the AUC value of our risk model is not the highest, similar to many previous risk models, our risk model can not only predict prognosis better but also serves as an independent prognostic model [48][49][50][51]. These results also suggest that we may need to further refine our models.…”
Section: Discussionsupporting
confidence: 67%
“…The patients in the low-risk group exhibited better prognoses in both internal and external datasets. Unlike many previous cervical cancer prognostic models trained and tested internally using the TCGA database, our validation extended to external datasets, providing a more comprehensive evaluation [40] , [41] , [42] . Furthermore, our risk model consistently achieved a 5-year AUC value of 0.7, distinguishing itself from many cervical cancer biomarkers that primarily predicted OS by excelling in predicting both OS and PFS [43] , [44] , [45] .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the crucial role of multigene signatures in predicting the prognosis of CC [37,38]. For instance, one study constructed a four immune-related gene model for the prediction of CC prognosis, Xie et al [39] constructed an eight-gene model to predict the prognosis of CC after radiotherapy, while another study established a model based on 70 genes to predict the prognosis of advanced CC [39][40][41].…”
Section: Discussionmentioning
confidence: 99%